2020
DOI: 10.1093/scan/nsaa146
|View full text |Cite
|
Sign up to set email alerts
|

Patients with anxiety disorders rely on bilateral dlPFC activation during verbal working memory

Abstract: One of the hallmarks of anxiety disorders is impaired cognitive control, affecting working memory (WM). The dorsolateral prefrontal cortex (dlPFC) is critical for WM, however it is still unclear how dlPFC activity relates to WM impairments in patients. Forty-one healthy volunteers and 32 anxiety (general and/or social anxiety disorder) patients completed the Sternberg WM paradigm during safety and unpredictable shock threat. On each trial a series of letters was presented, followed by brief retention and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…To our knowledge, neither the ToSP nor the threat of shock paradigm have yet been systematically utilized to study complex learning and memory performance. In fact, up to date, there are only reports that threat of shock improves performance accuracy in a simple Go-NoGo task 34 , 35 or modulates working memory performance 23 , 36 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, neither the ToSP nor the threat of shock paradigm have yet been systematically utilized to study complex learning and memory performance. In fact, up to date, there are only reports that threat of shock improves performance accuracy in a simple Go-NoGo task 34 , 35 or modulates working memory performance 23 , 36 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, anxiety can compromise complex information processing and storage in healthy and aged individuals, as well as in patients with anxiety disorders 6 , 8 , 10 , 18 22 . The threat of shock paradigm has been developed to model the hyperarousal and diffuse feelings of danger or threat which are characteristic for patients with pathological anxiety to investigate the impact of anxiety on basic cognitive and behavioral processes including perception, attention, concentration, face recognition, spatial and verbal working memory, decision making, impulsivity or defensive reflex activity 23 27 .…”
Section: Introductionmentioning
confidence: 99%
“…This is essential for balancing the stress response because anxiety and depression are associated with prefrontal cortex hypoactivity and lack of inhibitory neural mechanisms ( 52 ). tES is not only employed to modulate cortical excitability in a target region but also induces changes in the interconnected areas and cortico-subcortical circuits ( 24 , 53 , 54 ). A meta-analysis, which included 61 single-session, sham-controlled, crossover DLPFC tDCS studies, concluded that overall participants across trials and analyses revealed a small, significant effect of a-tDCS on improving RTs and accuracy in cognitive tasks ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up work employing a within-subjects manipulation of threat conditions (acute and sustained, along with no-threat) would be particularly informative with respect to directly comparing the effects of different threat types on cognitive performance and their relationship to individual difference factors. Such work could help to interface findings from the current work with an emerging literature regarding the effects of predictable and unpredictable threat on cognitive performance (Balderston et al, 2020;Grillon et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%